Ekspresi Kebahasaan terhadap Liyan pada Portal Hidayatullah.com: Critical Discourse Analysis - Hatta, Juparno; Sofia, Adib (LP2M UIN Sunan Kalijaga, 2024)
Discourse in the media is always interesting to observe because it is produced by members of society, contains people's lives, and is enjoyed by society. This paper sees discourse not just as an arrangement of ideas in letters, phrases, sentences and paragraphs, but as a form of linguistic expression of writers or media managers who have backgrounds and perspectives. The Hidayatullah.com portal is the discourse observed in this paper, especially in linguistic expressions regarding parties or figures that are considered the other. This paper, which is library research with an interpretative descriptive mechanism, uses critical discourse analysis conceptualized by Norman Fairclough. This paper sees that Hidayatullah.com contains linguistic expressions that form demarcations through certain stereotypes of the other. Judging from linguistic expression, this portal builds social categories in the form of in-group-love and out-group-hate and in the context of talking about others and constructing other's identities in the second category. Furthermore, this paper reveals the background and perspective built through discourse in the media. [Wacana dalam media selalu menarik untuk diamati karena diproduksi oleh anggota masyarakat, memuat kehidupan masyarakat, serta dinikmati oleh masyarakat. Tulisan ini melihat wacana bukan sekadar susunan ide dalam huruf, frasa, kalimat dan paragraf, melainkan sebagai wujud ekspresi kebahasaan penulis atau pengelola media yang memiliki latar belakang dan perspektif. Portal Hidayatullah.com merupakan wacana yang diamati dalam tulisan ini, khususnya dalam ekspresi kebahasaan mengenai pihak atau figur yang dianggap the other atau liyan. Tulisan yang bersifat library research dengan mekanisme deskriptif interpretatif ini menggunakan critical discourse analysis atau analisis wacana kritis yang dikonsep oleh Norman Fairclough. Tulisan ini melihat Hidayatullah.com memuat ekspresi kebahasaan yang membentuk demarkasi melalui stereotipe tertentu kepada liyan. Dilihat dari ekspresi kebahasaan, portal ini membangun kategori sosial dalam bentuk in group-love dan out group-hate dan dalam konteks pembicaraan tentang liyan serta mengkonstruksi identitas liyan dalam kategori yang kedua. Selanjutnya, tulisan ini mengungkap latar belakang dan perspektif yang dibangun melalui wacana dalam media tersebut.]